2021
DOI: 10.1016/j.jnma.2020.09.152
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Clinical Pharmacology: Relevance to COVID-19 Pathogenesis

Abstract: ▪▪▪.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
(35 reference statements)
0
4
0
3
Order By: Relevance
“…Dark skin, through the presence of abundant melanin, protected humans living in Africa, southern India, and other parts of Asia against strong UVB, which causes severe sunburn, damages DNA, and destroys skin folate [ 3 , 20 , 21 , 22 ]. According to a widely accepted hypothesis, people in ancient times moved from low to higher latitudes, and skin pigment evolved (by several mutations) to be lighter, depending on distance from the equator, permitting more efficient production of vitamin D [ 3 , 23 , 24 , 25 , 26 ]. Others have suggested that lighter skin resulted from the acquisition of genetic variants from populations that immigrated into northern Europe, but this is still compatible with production of vitamin D being the initial selective factor for these variants [ 27 ].…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…Dark skin, through the presence of abundant melanin, protected humans living in Africa, southern India, and other parts of Asia against strong UVB, which causes severe sunburn, damages DNA, and destroys skin folate [ 3 , 20 , 21 , 22 ]. According to a widely accepted hypothesis, people in ancient times moved from low to higher latitudes, and skin pigment evolved (by several mutations) to be lighter, depending on distance from the equator, permitting more efficient production of vitamin D [ 3 , 23 , 24 , 25 , 26 ]. Others have suggested that lighter skin resulted from the acquisition of genetic variants from populations that immigrated into northern Europe, but this is still compatible with production of vitamin D being the initial selective factor for these variants [ 27 ].…”
Section: Current Status Of Knowledgementioning
confidence: 99%
“…The effective dose of VD3 to provide at least partial protection against the effects of SARS-CoV-2 infection is unknown and is under investigation. Serum VD3 levels are a delayed marker of whole-body VD3 status as tissue reserves are depleted before serum VD3 levels fall below normal [71]. Clinical trials of oral vitamin D supplementation in COVID-19 patients are registered at clinicaltrials.gov, for example, randomized trial of high-dose versus standard-dose VD3 in high-risk COVID-19 patients [72].…”
Section: Investigation Into the Role Of Vitaminsmentioning
confidence: 99%
“…Дослідження Огляди реакція на незгорнуті білки -UPR (unfolded protein response) [55,56]. Білки експонують гідрофобні пептидні послідовності, які в нормі захищені від внутрішньоклітинного водного середовища, коли вони денатуровані чи неправильно складені.…”
Section: вітамін D і серцево-судинна системаunclassified
“…При потраплянні гідрофобних сегментів білка в багату білками цитоплазму, процеси клітинного обміну ускладнюються. Це викликає добре відому реакцію на метаболічний стрес, яка виникає при пошкодженні клітин або при захворюваннях, і метою якої є видалення незгорнутих білків та збереження життєздатності клітин [55,56].…”
Section: вітамін D і серцево-судинна системаunclassified
See 1 more Smart Citation